2014
DOI: 10.1177/0163443714527567
|View full text |Cite
|
Sign up to set email alerts
|

Start making sense: a three-tier approach to citizen journalism

Abstract: This commentary considers citizen journalism emerging from the Syrian Civil War and argues that its usefulness is dependent on an “interpreter tier” of user-generated media analysts. In contrast to discourse celebrating more direct forms of citizen journalism, the piece emphasizes the importance of intermediary layers of meaning-making as the means by which complex fields of amateur information can be made intelligible. This “interpreter tier,” although often ignored in popular and scholarly discourse, takes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…The Huffington Post goes quite a bit further, identifying him as "the one-man intelligence unit that exposed the secrets and atrocities of Syria's War" (Bosker, 2013). Numerous scholarly analyses of the Syrian Civil War (Miller & Sienkiewicz, 2012;Wall & el Zahad, 2014;Sienkiewicz, 2014;Gohdes, 2014) have complicated this perspective, highlighting the profoundly collaborative nature of the work that Higgins and his peers have engaged in while covering the conflict. Yet, Higgins' stardom played a crucial role in organizing and attracting digital laborers to the case of MH17.…”
Section: Bellingcatmentioning
confidence: 99%
See 1 more Smart Citation
“…The Huffington Post goes quite a bit further, identifying him as "the one-man intelligence unit that exposed the secrets and atrocities of Syria's War" (Bosker, 2013). Numerous scholarly analyses of the Syrian Civil War (Miller & Sienkiewicz, 2012;Wall & el Zahad, 2014;Sienkiewicz, 2014;Gohdes, 2014) have complicated this perspective, highlighting the profoundly collaborative nature of the work that Higgins and his peers have engaged in while covering the conflict. Yet, Higgins' stardom played a crucial role in organizing and attracting digital laborers to the case of MH17.…”
Section: Bellingcatmentioning
confidence: 99%
“…Instead, Avakov's communiqué is better understood as a job posting or, perhaps more accurately, a call for volunteers. The murky BUK video was an intriguing puzzle, irresistible to the skilled, forensic online video investigators described by Sienkiewicz (2014) as the global "interpreter tier" that plays a key mediating role between citizen video makers and mainstream press outlets.…”
mentioning
confidence: 99%
“…This might be related to the fact that we presented UGC published in a professional journalistic context, where one could expect information to be vetted. Although most journalists try to verify such information, examples in the past have shown that they do not always manage to do so (Sienkiewicz 2014). As previously discussed, most journalists have taken to explicitly stating whether or not UGC-provided information could be verified or not.…”
Section: Discussionmentioning
confidence: 99%
“…Worrall (2016). trend of citizen journalism and UGC that became prominent among the Arab Spring movements (Sienkiewicz 2014). As it had been since the beginning of the conflict, the role of UGC remains a key element in the coverage of the conflict, particularly in challenging the regime narratives, thus becoming a target for a counter-information strategy.…”
Section: The Disinformation Campaign Against the White Helmetsmentioning
confidence: 99%
“…On top of creating an unfiltered and realistic account of the events, this new form of war journalism also lent itself to propagandistic ends by means of curatorial hubs which served as filters between activists and the mainstream media (Trombetta 2012;Sienkiewicz 2014). The Syrian regime exploited these new conditions of mediation to spread propagandistic narratives, via its official news agency and government-friendly television networks, often circulating unverifiable or falsified amateur videos.…”
Section: Introductionmentioning
confidence: 99%